2017
DOI: 10.1590/s0004-2803.201700000-10
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Motility in Men and Women Evaluated by High-Resolution Manometry

Abstract: -Background -Esophageal motility has been described in the literature as having differences between men and women. Most of these investigations use the water perfusion method for esophageal manometry. In this investigation the esophageal motility of men and women was compared with high-resolution manometry of the esophagus. Objective -To compare the esophageal motility of men and women with the high-resolution manometry method for esophageal manometry, performed in the sitting position. The hypothesis was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…However, this variation between sexes is not consistent in other literatures 26 . The low IRP‐4 s may be linked to lower LES pressure observed in male patients or may be due to the effect of raised gastroesophageal gradient from obesity because we observed the same effects in obese state, but the exact reason is unknown 25,26 . At this juncture, whether to have different thresholds for men or women is unclear, and neither does Chicago classification v3.0 discriminate between the two, but future larger population‐based studies may be able to address the gender differences and to inform future classifications.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…However, this variation between sexes is not consistent in other literatures 26 . The low IRP‐4 s may be linked to lower LES pressure observed in male patients or may be due to the effect of raised gastroesophageal gradient from obesity because we observed the same effects in obese state, but the exact reason is unknown 25,26 . At this juncture, whether to have different thresholds for men or women is unclear, and neither does Chicago classification v3.0 discriminate between the two, but future larger population‐based studies may be able to address the gender differences and to inform future classifications.…”
Section: Discussioncontrasting
confidence: 81%
“…Besides, a similar increment with viscous swallow was observed with DL, and perhaps, the greater intrabolus pressure from viscous materials causes a delay in distal esophageal clearance 15 . It is worthy to note that although the 95th percentile value of DL reported by the Chicago classification was 7.6 s, 30,31 ours and the European population found that 8.5 s may be an acceptable threshold 26 . Provocative swallows with solids like bread may have been a better challenge than liquid swallows with the intention to unmask underlying motor diseases 3 .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Also, differences in swallowing between men and women is a matter of controversy (17) , and may not be clinically relevant among patients with achalasia. In healthy subjects, gender does not seem to influence esophageal motility (18) .…”
Section: Discussionmentioning
confidence: 82%
“…Those authors found a significantly higher limit of IRP in female participants (18.96 vs 14.46 mmHg), even after adjustment for BMI . Similarly, a recent study using 32‐channel solid‐state HRM in 22 healthy volunteers (10 male, 12 female) found a statistically non‐significant pattern of higher median IRP in women than in men (8.2 vs 5.0 mmHg) . The reason for higher IRP‐4s values in females remains unclear.…”
Section: Discussionmentioning
confidence: 90%